(untitled) (CAHIERS MAGELLANES-NS, 2024)
Organ donation is the surgical removal of an organ from one body to another or from a donor site on the patient's own body for the purpose of replacing the recipient's damaged or absent organ. Organ donation is a medical industry as it has helped in saving the lives of those who would have died otherwise. The numbers of people requiring the life saving transplants continue to rise faster than the number of available donors. Organ donation is a life saving act based on ones humanity. But some are unaware of the organ donation and the further proceedings. So the researcher has selected this topic to assess the effectiveness of structured teaching program regarding organ donation. This would help to improve the awareness of the public and thereby to enhance the number of organ donors. The purpose of the study was to assess the level of knowledge and attitude regarding organ donation among B.Sc.Nursing First year & Second year students in a selected Nursing College at Ujjain, M.P The study findings can help the B.Sc.Nursing First year & Second year students to improve their knowledge and attitude towards organ donation and can be a donor in their future. The objective of the study was to assess the knowledge and attitude of organ donation among the BSc. nursing First year & Second year students. A descriptive research approach with descriptive research design was used for the present study. The target population for the study was B.Sc. Nursing First year and Second year students. Sample size was 100. The obtained data was analysed based on objective and hypothesis by using descriptive and inferential statistics and hypothesis were tested at 0.5 level of significance. The result of the study indicate that majority of the B.Sc.nursing First year & Second year students 67 (67%) have moderate level of knowledge. 78 (78%) of the B.Sc.nursing First year & Second year students have unfavourable attitude. The present study concluded that the majority of the B.Sc. nursing First year & Second year students have moderate level of knowledge and an unfavourable attitude towards organ donation